FICA Taxation of Post-Employment Benefits: A Statutory Puzzle and Sociopolitical Conundrum - Amanda Stein (Washington University Law Review, 2013)
In the wake of a brief but contentious span that has included a presidential election, fiscal cliff and government shutdown, the probability of a congressional answer to an important question that is sociopolitically confounding—but not operationally urgent—was remote. Instead, it is the Supreme Court that will take up the issue at hand, at its heart a question of statutory interpretation: whether severance payments are “wages” for purposes of the FICA tax. As a legal issue, this may appear simple on its face, but the arguments are technical and require a complex analysis of key regulations, multiple sections of the Internal Revenue Code, and existing case law. As a social and political question, it is even more complex; with strong interests on both sides, the implications are significant. This Note first contextualizes the question to emphasize the importance of a clear resolution and then sets out to discuss in detail the analytical bases for a circuit split created by opposing Federal Circuit and Sixth Circuit opinions on this question.
Keywords: In re Quality Stores; CSX Corporation